Temperature-sensitive ribonucleic acid polymerase mutant of Salmonella typhimurium with a defect in the beta' subunit. - Young, B S (1976)
Localized mutagenes of Salmonella typhimurium followed by a [3H]uridine enrichment procedure yielded a temperature-sensitive strain with a mutation in the rpo region of the chromosome. Ribonucleic acid (RNA) polymerase (EC 2.7.7.6; nucleoside triphosphate: RNA nucleotidyltransferase) purified from this mutant was considerably less active at the nonpermissive temperature than wild-type enzyme. Furthermore, the enzyme from this mutant, unlike RNA polymerase of previously isolated temperature-sensitive mutants, was as thermostable as wild-type enzyme when preincubated at 50 degrees C. Subunit reconstitution experiments have shown that the temperature sensitivity is caused by an alteration in the beta' subunit of the enzyme.